2019
DOI: 10.3889/oamjms.2019.318
|View full text |Cite
|
Sign up to set email alerts
|

Utilisation of Cryolipolysis among Asians: A Review on Efficacy and Safety

Abstract: Cryolipolysis is a non-invasive fat reduction method that is capable of reducing subcutaneous fat significantly without damaging surrounding tissues, by applying cold temperature to induce adipocyte apoptosis. Most of the clinical studies in cryolipolysis were conducted in the Caucasian population, and only a few numbers in Asian, who has darker skin with Fitzpatrick skin type III to V. Higher rate of pigmentary changes were reported with the use of cryotherapy in darker skin. Therefore, this report is aimed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 31 publications
2
18
0
3
Order By: Relevance
“…Cryolipolysis is an effective method for noninvasive local subcutaneous fat reduction with highly selective cold-induced adipocyte apoptosis without harming the surrounding tissues [16,44,45]. Thus, the reshaping effect of Cryolipolysis in addition to the effect of low caloric diet enhanced significant improvements in body mass index, lipid profile, and liver enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…Cryolipolysis is an effective method for noninvasive local subcutaneous fat reduction with highly selective cold-induced adipocyte apoptosis without harming the surrounding tissues [16,44,45]. Thus, the reshaping effect of Cryolipolysis in addition to the effect of low caloric diet enhanced significant improvements in body mass index, lipid profile, and liver enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…Putra et al [18] performed a review of the literature regarding cryolipolysis in Asian populations and reported that cryolipolysis has displayed good efficacy and safety in Asian patients, although only a few studies, with relatively few subjects, have been performed on Asian populations. In our study, the authors evaluated the efficacy and safety of cryolipolysis based on results obtained from a sufficient number of Asian patients and demonstrated that cryolipolysis has the same efficacy and safety among Asian patients as Putra et al argued.…”
Section: Discussionmentioning
confidence: 99%
“…The advent of new technology such as noninvasive body-contouring devices has changed the business of surgical treatments and provided new options for addressing fat reduction. Lipolysis devices such as radiofrequency [ 4 ], cryolipolysis [ 5 7 ], ultrasound [ 8 , 9 ], and lasers [ 1 , 3 , 10 13 ] are now being used worldwide as alternative procedures to remove fat in unwanted areas with a better safety profile compared with liposuction and other surgical procedures [ 1 13 ]. Each device has its own mechanism and efficacy profile [ 4 – 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy was comparable to the present study, which also demonstrated reduction at 3 and 6 months post-treatment. Cryolipolysis works by inducing adipocyte apoptosis and inflammatory response using cold temperatures without damaging surrounding areas [ 5 7 ], while laser lipolysis generates controlled hyperthermia using a specific wavelength and optimal power in the subcutaneous layer and causes photothermal reaction that destroys adipocytes and stimulates inflammatory response [ 10 , 13 ]. In the study by Decorato et al., hyperthermic laser lipolysis was comparable to cryolipolysis in average fat reduction at 3 and 6 months after treatment [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation